Development and Design of an Optimal Fuzzy Logic Two Degrees of Freedom-Proportional Integral Derivative Controller for a Two-Area Power System Using the Bee Algorithm - Sitthisak Audomsi; Supannika Wattana; Narongkorn Uthathip; Worawat Sa-ngiamvibool (Energies, 2025)
This study introduces a fuzzy logic-based two-degree-of-freedom PID (FL2DOF-PID) controller that is optimized using the Bee Algorithm (BA) to control the load frequency in a two-area linked power system that has both reheat thermal power plants and hydro power plants. To test how well it works, MATLAB/Simulink simulations compared it with PID, 2DOF-PID and fuzzy PID controllers, looking at overshoot, undershoot, settling time, steady-state error and the integral of absolute error (IAE). The results showed that FL2DOF-PID had the lowest RMSE (0.0054, 0.0089) and MAE (0.0041, 0.0065), as well as the smallest IAE (0.1308) and the smallest overshoot (69.3% less). It also had the fastest settling time (5.1528 s) and the smallest IAE (0.1338 less). These results showed that it works to reduce frequency changes, improve power flow stability and make the whole system more reliable under changing conditions.